SCHOOL VIOLENCE : CONTRIBUTIONS OF PROFESSIONAL PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
This brief outline of the theory about school violence dialoguing with education and the professional practice of physical education , allowed us to identify how this professional can help in preventing and coping with the violence in and against the school . Conflict mediation can be one of the proposals to pacify the school space from a practice of negotiation established within the school , especially in the groups of pupils , through the idea of ??peer mediation , in order to create possibilities interaction among students by developing a supportive environment , humanistic and cooperative , so that the actions of this person may be directed to a culture of peace and emancipatory actions, knowing that these actions have to be in harmony with the proposing institutio, articulated with the government.
Keywords: School; Violence; Physical Education